Wpływ substancji organicznych pochodzenia roślinnego na kiełkowanie nasion i rozwój siewek sosny zwyczajnej Pinus sylvestris L. - Kwiatkowski, Damian; Knapek, Jarosław; Słowiński, Krzysztof (Leśne Prace Badawcze, 2019)
In this article we analysed the influence of plant-based organic admixtures on the germination process of seeds and the early development of Scots pine Pinus sylvestris L. seedlings. The intensity of dumpin-off diseases within the culture was recorded after applying each of the admixtures. Organic material of nettle Urtica dioica L., softwood litter, hardwood litter and peat were applied to the nursery substrate in two ways, either as an admixture in crushed form or in granulated form. None of the introduced admixtures influenced the germination of seeds or the survival rate of pine seedlings positively. The best results were obtained with a substrate without admixtures used as a control, which is the most common nursery substrate. The worst seed germination rate was observed on the substrate enriched with the organic material from nettles. In pots with granulated organic material from hardwood litter, significantly more seedlings showed signs of post-emergence dermatitis. In all other cases, there was no clear difference between the crushed or granulated admixture in either germination or survival of seedlings. We furthermore demonstrated that the process of granulating plant material leads to an approximately 10-fold increase in the bulk density of the granulated substance, which translates directly into volume reduction.